Platelets retain inducible alpha granule secretion by P‐selectin expression but exhibit mechanical dysfunction during trauma‐induced coagulopathy. (18th March 2019) - St. John, Alexander E.; Newton, Jason C.; Martin, Erika J.; Mohammed, Bassem M.; Contaifer, Daniel; Saunders, Jessica L.; Brophy, Gretchen M.; Spiess, Bruce D.; Ward, Kevin R.; Brophy, Donald F.; López, José A.; White, Nathan J.
Abstract : Essentials Platelets in trauma‐induced coagulopathy (TIC) are impaired, but the mechanism is not known. We performed comprehensive longitudinal platelet function testing in trauma patient samples. Platelets in TIC are widely impaired early after injury, but platelet activatability is intact. This suggests a mechanism of transient platelet cytoskeletal/integrin dysfunction during TIC. Summary: Background: Trauma‐induced coagulopathy (TIC) is a common and deadly bleeding disorder. Platelet dysfunction is present during TIC, but its mechanisms remain unclear. Platelets are currently thought to become "exhausted, " a state in which they have released their granule contents and can no longer aggregate or contract. Methods: This prospective observational cohort study tested the hypothesis that platelet exhaustion is present during TIC and characterized the early time course of platelet dysfunction. Blood was collected from 95 adult trauma patients at a Level I trauma center at time of Emergency Department arrival and several time points over 72 h. Platelet activation state and function were characterized using CD62P (P‐selectin) and PAC‐1 surface membrane staining, platelet function analyzer (PFA‐100), aggregometry, viscoelastic platelet mapping, and, to test for exhaustion, their ability to express CD62P after ex vivo adenosine diphosphate (ADP) agonism. Platelet function was compared between patients with and without TIC, defined by prothrombin time ≥18 s. Results: Platelets in TIC showed no initial increase in their level of surface activation markers or impairment of their capacity to express CD62P in response to ADP stimulation. However, TIC platelets were impaired in nearly all functional assays, spanning adhesion, aggregation, and contraction. These effects largely remained after controlling for platelet count and fibrinogen concentration and resolved after 8 h. Conclusion: The TIC platelets exhibit early impairment of adhesion, aggregation, and contraction with retained alpha granule secretion ability, suggesting a specific mechanism of cytoskeletal or integrin dysfunction that is not a result of more general platelet exhaustion.